Hubungan Usia Ibu dan Kurang Energi Kronik (KEK) dengan Kejadian Anemia pada Ibu Hamil di Puskesmas Putri Ayu Kota Jambi - Hariyanti, Reni; Azahra, Nanda Dilla; Sulastri, Sulastri; Monica, Olivia Tri (Jurnal Ilmiah Universitas Batanghari Jambi, 2024)
The aim of this study was to determine the relationship between the prevalence of anemia in pregnant women at the Putri Ayu Community Health Center in 2024 with maternal age and KEK. This research is quantitative retrospective. The population in this study were all pregnant women who had their pregnancies checked at the Putri Ayu Community Health Center in 2022 with a total of 65 respondents. Investigate information using the chi-square test. The results of the research show that there is no relationship between maternal age and the frequency of pallor in pregnant women and there is a relationship between KEK and the occurrence of frailty in pregnant women at the Putri Ayu Community Health Center, Jambi City in 2024.